A Factor Analysis of the Perceived Value of Certification Tool for Nurse Educators: Evidence for Construct Validity. Issue 3 (May 2018) - Barbé, Tammy; Kimble, Laura P.
Abstract: AIM: The purpose of this study was to examine construct validity of the Perceived Value of Certification Tool for Nurse Educators (PVCT-NE). BACKGROUND: Preliminary testing of the PVCT-NE demonstrated content validity and strong evidence of internal consistency reliability. Construct validity evidence for the tool is lacking. METHOD: Using data from a descriptive study about nurses' perceived value of nurse educator certification, exploratory factor analysis was used to examine whether the factor structure of the PVCT-NE was consistent with the two-factor structure reported for the original PVCT. RESULTS: Data ( n = 221) were analyzed using principal components analysis to identify factors. The observed two-factor solution and individual item loadings in this sample were consistent with the original PVCT's intrinsic and extrinsic value subscales and accounted for 64 percent of the total instrument variance. CONCLUSION: Overall, the PVCT-NE is a valid tool to measure perceived value of certification in nurse educators.